Multiple-choice and cloze procedures in reading tests: what do they really measure? - Retorta, Miriam Sester (The ESPecialist, 2012)
This article presents the results of a study carried out from July 1995 to August 1996, with the aim of finding out what mental process(es) a testee goes through while taking multiple-choice and cloze test. Twentythree proficient non-native English speakers were asked to answer three multiple-choice tests and one cloze test, and write a report on how they reached the answers. Two flow-charts of strategies used to achieve the correct answers were then designed. It was found that not only do testees use reading strategies but they also get engaged in a complex task of designing strategies to arrive at the correct answers.